Watermelon peel, xylanase and -glucanase in diets for Japanese quails (Research, Society and Development, 2020)
The objective was to evaluate the inclusion of 5% of the bran of the watermelon peel with and without the inclusion of xylanase and β-glucanase in the feeding of Japanese quails on performance, egg quality, biochemical profile and biometrics. 120 female quails of the species Coturnix coturnix japonica were used. The design was completely randomized in a 2 x 2 factorial scheme, with six replications, containing six birds per cage. The treatments consisted of: T1 - Corn and soybean meal, T2 - T1 + carbohydrates, T3 - T1 + 5% watermelon bran, T4 - T3 + carbohydrates. There was a significant effect (p> 0.05) increasing the feed intake for diets without inclusion of enzyme, the feed conversion per dozen eggs produced improved with the use of enzymes. As egg quality, the use of watermelon skin bran with enzymes increased height, index, color and reduced the pH of the yolk. Albumen was affected in its diameter and pH, while the shell was affected in its thickness in diets with the addition of enzyme. It is concluded that the bran of the watermelon peel can be used at the level of 5% with enzymes, without negatively altering performance, egg quality, biometrics and blood analysis.